1993
DOI: 10.1007/bf00185949
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of semitendinosus muscle in the dog

Abstract: In this study the differentiation of postnatal muscle fibres in dog semitendinosus muscle has been characterized. Several histochemical techniques for myosin ATPase and metabolic activity were used in animals aged between 1 day and 2 months. The results show that at birth there are two types of fibre, whose ATPase activity gradually changes during postnatal development, so that several types of fibre can be identified after 2 months. These finally become the four types of the adult: I, IIA, IIDog, IIC. The mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…In this study, the predominant fiber type was the fast twitch oxidative IIA fibers, followed by Type I and IIX. This finding was evident in both the TB and VL muscle groups and is supported by previous research on dogs, which included muscle groups such as the semitendinosus , longissimus dorsi , gluteus medius , biceps femoris , TB, and VL (Acevedo & Rivero, 2006; Braga et al, 2016; Braund et al, 1982; Guy & Snow, 1981; Latorre et al, 1993; McKenzie et al, 2005; Strbenc et al, 2004; Toniolo et al, 2007). Acevedo and Rivero (2006) found that dog muscle fibers expressing MHC IIX were only found in the latissimus dorsi , gluteus medius , and semitendinosus (averaging 8% of the muscle fibers).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In this study, the predominant fiber type was the fast twitch oxidative IIA fibers, followed by Type I and IIX. This finding was evident in both the TB and VL muscle groups and is supported by previous research on dogs, which included muscle groups such as the semitendinosus , longissimus dorsi , gluteus medius , biceps femoris , TB, and VL (Acevedo & Rivero, 2006; Braga et al, 2016; Braund et al, 1982; Guy & Snow, 1981; Latorre et al, 1993; McKenzie et al, 2005; Strbenc et al, 2004; Toniolo et al, 2007). Acevedo and Rivero (2006) found that dog muscle fibers expressing MHC IIX were only found in the latissimus dorsi , gluteus medius , and semitendinosus (averaging 8% of the muscle fibers).…”
Section: Discussionsupporting
confidence: 80%
“…Over the past 50 years, a handful of studies have been published that investigated the muscle composition and metabolic characteristics of dogs, each with varying research questions and results (Acevedo & Rivero, 2006; Braga et al, 2016; Braund et al, 1982; Gunn, 1978; Guy & Snow, 1981; Kuzon et al, 1989; Latorre et al, 1993; McKenzie et al, 2005; Snow et al, 1982; Strbenc et al, 2004; Toniolo et al, 2007). Overall, the muscle of dogs seem to harbor a prevalence of Type I and IIA fibers with a higher oxidative capacity compared to glycolytic capacity.…”
Section: Introductionmentioning
confidence: 99%
“…After a few weeks of age they differentiated into other types known in adult animals, i.e. I, IIA and IIDog (Braund & Lincoln, 1981; Latorre et al. 1993b).…”
Section: Introductionmentioning
confidence: 99%